2009
DOI: 10.1002/jcb.22097
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals upregulation of RKIP in S‐180 implanted BALB/C mouse after treatment with ascorbic acid

Abstract: Tumor cells have an invasive and metastatic phenotype that is the main cause of death for cancer patients. Tumor establishment and penetration consists of a series of complex processes involving multiple changes in gene expression. In this study, intraperitoneal administration of a high concentration of ascorbic acid inhibited tumor establishment and increased survival of BALB/C mice implanted with S-180 sarcoma cancer cells. To identify proteins involved in the ascorbic acid-mediated inhibition of tumor progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Pharmacologic ascorbate treatment (1.5 g/kg injected intraperitoneally) upregulated hepatic expression of rapidly accelerated fibrosarcoma (Raf) kinase inhibitory protein (RKIP) and annexin A5 in a S-180 sarcoma xenograft model, coincident with decreased tumor growth and increased survival rate relative to controls (61). Messenger RNA (mRNA) levels were also upregulated, suggesting a transcriptional control mechanism.…”
Section: A Role For Transcription Factors and Signal Transduction Patmentioning
confidence: 99%
“…Pharmacologic ascorbate treatment (1.5 g/kg injected intraperitoneally) upregulated hepatic expression of rapidly accelerated fibrosarcoma (Raf) kinase inhibitory protein (RKIP) and annexin A5 in a S-180 sarcoma xenograft model, coincident with decreased tumor growth and increased survival rate relative to controls (61). Messenger RNA (mRNA) levels were also upregulated, suggesting a transcriptional control mechanism.…”
Section: A Role For Transcription Factors and Signal Transduction Patmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that some of the effects associated with AA are at transcriptional level (Park et al 2009; Shin et al 2004; Belin et al 2009). Despite a number of solid indications, the mechanism by which ascorbic acid affects gene expression is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…K alone exhibited an inhibitory effect only at the highest concentration tested and following 48 Another potential explanation for the heterogeneous effect observed in different breast cancer cell lines upon treatment with A and K in the present study may be the cell length and conformation of telomeres, which may be affected by the concentration of K + in the different cell lines tested (61). In healthy cells, each cell replication results in 50-200 bp loss of the telomere (62).…”
Section: Discussionmentioning
confidence: 59%
“…A possesses both pro-oxidant and anti-oxidant properties (42)(43)(44)(45)(46)(47)(48)(49)(50). Although the preventive anti-cancer effect of A results from its anti-oxidant properties (42), previous in vitro studies and mouse models have demonstrated that A is able to inhibit cell proliferation in various types of cancer due to its ability to induce the production of H 2 O 2 (43-49) without being toxic to non-cancerous cells (43,50).…”
Section: Discussionmentioning
confidence: 99%